2007
DOI: 10.1111/j.1365-2109.2006.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acids and fatty acids of the common octopus, Octopus vulgaris, in relation to the growth rate

Abstract: The aim of this study was to investigate changes in the ribonucleic acid (RNA)/deoxyribonucleic acid (DNA) ratio and the fatty acid composition of cultured Octopus vulgaris (50^750 g) in relation to recent (last 30 days) speci¢c growth rate (SGR).Wild animals (80^500 g), collected in the ¢eld throughout the year (Aegean Sea, Mediterranean), were also examined for the aforementioned biochemical parameters. Octopuses were reared in a closed seawater system at three di¡erent temperatures (15, 20 and 25 1C). The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Indeed, a decrease on lipid content associated to increasing size was also observed in wild and reared O. vulgaris (Navarro and Villanueva 2003; Biandolino et al 2010). Main fatty acids in octopus muscle are in agreement with previous data (Navarro and Villanueva 2003; Rosa et al 2004; Miliou et al 2007; Prato et al 2010). Decrease in ARA and DHA in octopus reared in Trial 1 may be related to higher demand of these fatty acids induce by high growth rates in comparison to specimens reared in Trial 2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, a decrease on lipid content associated to increasing size was also observed in wild and reared O. vulgaris (Navarro and Villanueva 2003; Biandolino et al 2010). Main fatty acids in octopus muscle are in agreement with previous data (Navarro and Villanueva 2003; Rosa et al 2004; Miliou et al 2007; Prato et al 2010). Decrease in ARA and DHA in octopus reared in Trial 1 may be related to higher demand of these fatty acids induce by high growth rates in comparison to specimens reared in Trial 2.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, higher biomass increments and lower A‐FCR induced by the individual rearing system in both trials were related to higher survival than in group reared octopuses. These results underline the positive effect of individual rearing on octopus survival, also observed in O. vulgaris reared individually in tanks (Petza et al 2006; Miliou et al 2007; Cerezo Valverde et al 2008; García Garrido et al 2011) and in net cages inside tanks (Biandolino et al 2010; Estefanell et al 2009; Prato et al 2010). For this reason, the use of individual rearing is a common practice in other high price and highly cannibalistic farmed species, such as crab Portunus sanguinolentus and lobster, Homarus gammarus (Nicholson et al 2008; Perez et al 2010).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Besides, other authors suggested that dietary lipids for cephalopods must be rich in phospholipids and cholesterol (Navarro & Villanueva ). Regarding fatty acid profile in octopods, several authors underlined the importance of polyunsaturated fatty acids (PUFA), especially EPA (20:5n‐3) and DHA (22:6n‐3) (Navarro & Villanueva , ; Miliou, Fintikaki, Tzitzinakis, Kountouris & Verriopoulos ; Miliou, Fintikaki, Kountouris, Tzitzinakis & Verriopoulos ; García Garrido, Domingues, Navarro, Hachero‐Cruzado, Garrido & Rosas ; García Garrido et al . ).…”
Section: Introductionmentioning
confidence: 99%